(untitled) (Journal of the College of Education for Women, 2019)
The study falls in Five chapters as follows:Chapter One : definition of the Study including:1. The problem of the study: the current study tries to answers two questions;First: the effectiveness of the performance of the applicants in the department of QuranSciences and Islamic Education in the colleges of Education according the point of view oftheir supervisors.Second: what is the future vision for teacher training according to the assessment of theperformance of the applicant students?2. The importance of the study: the application or the field training is of an important rolein the process of training the students for teaching; as it is considered the real scale ofsuccess in the processes of academic and professional preparing of the students. Throughwhich it is possible to assess the success of the students and the college in the process oftraining.If it is well prepared and carried out, the program of application is going to be a greatopportunity to achieve what the students have studied I the stage of training as the skillsand information and tendencies. It is a chance to perform the operation and living the reality on hand and the training for the future profession in the near future on the otherhand.The researcher believes that the importance of the study, ( the evaluation of the applicantstudentsaccording to the point of view of their supervisors in the colleges of education inthe university of Baghdad), lies that the profession of the teacher in the modern developingeducation that is expected for the 21st century that is distinguished with change. The role ofthe teacher is going to change too. Therefore the training of the students and preparingthem inside the educational organization and outside it is a very important and necessaryfor developing the students’ competence and skills to help them be ready to deal with thechallenges and the innovations successfully.Hence, comes the importance of presenting a future vision to the process of trainingteachers. Rather than being a kind of a prophecy, predicting the future is a kind of turningthe ground for the good seeds that might grow to good plants tomorrow. It is important tounderstand that the life of the future would never be like today’s life exactly like futureeducation that would never be like of today’s. The look for the future and the try toparticipate in forming its picture is the desire of Man since eternity. The educationalprocess in general is the preparation for the future leading to the saying "any educationalsystem can never raise upper than the standard of its teachers."3. The objectives of the study:1. The evaluation of the applicant- student of the department of Quran Sciences andIslamic education in the colleges of education in the university of Baghdadaccording to the point of view of their supervisors.2. Presenting a new future vision to train the teachers of Iraq according to the firstobjective.4. The limitation of the study:1. the students of the fourth stage as applicants in the departments of Quran Sciencesand Islamic education in the colleges of education in the university of Baghdad in2008-2009 who are going to teach the subject of the Holy Quran and IslamicEducation in the intermediate and secondary schools.2. the scientific and educational supervisors in the colleges of education an theheadmasters of the schools ( the school administrative) in which the students are todo their practical application ( the sample of the study).5. The terminology limitation: the researcher clarifies the terms used in the title and thepractical term in it.Chapter Two : former studies: the researcher points out many of the former studies thatapproaches the current study especially those related to the structure of the tool of studyand explaining the results.Chapter Three: the study method and its procedures: the study depends on the analyticaland descriptive method to achieve the tow objectives of the study following a group ofprocedures represented in specifying the society of the study and its sample. The sample isof the fourth stage of the department of Quran Sciences and Islamic Education in thecolleges of education in the University of Baghdad of (189) female and male students,among which 48 are chosen to be the sample of the study, with a rate of 25% of thesociety. The researcher believes that the above rate is a good one to represent a smallcommunity of (!-500) of which it is possible to take a sample between (20-25%). Theresearcher depends on the open questionnaire and taking information from former studies and reviewing literature. The researcher has checked the validity and reliability of themethod. The chapter includes also the statistical aids used in analyzing the results.Chapter Four: the results of the study and their analysis; the study depends on a detailedstyle in stating the results according to the point of view of the educational supervisors firstand then according to the scientific supervisors, third according to the headmasters field;according to the field and items of each domain. The analysis of the results has concentrateon the first and the last item of each field. In addition to that, the study compares betweenthe results of the opinions of the educational and scientific supervisors and finds nodifferences with any statistical significance in them.Chapter Five: conclusion, recommendation, and suggestions: according to the results thestudy presents a number of conclusion:1. The practical application is an essential part in training teachers, as it is a basicelement and a corner rock to fill the gap between the theoretical side and thefield work or practical side.2. To ignore the practical side by the responsible people in the educational andscientific field can be a big challenge that faces education in Iraq.3. Therefore, it is a very urgent necessity to review the programs of trainingteachers to cope with the rapid changes in the field of educational economicsand technology.The study presents a number of recommendation:1. Make use of former experiments of the world in the process of training teachers.2. Confirm the principle of balance between the program and the items related toeducational, scientific, and cultural training.3. Confirm the importance of the practical performance in the process of trainingteachers starting form the first year up to the end of the program of training.The current study presents a number of suggestions:1. Evaluating teacher training programs according to the point of view of theapplicants students.2. Studying the problems and difficulties that face the applicant students in thedepartments of Quran Sciences in the colleges of education in Iraq and theirtendency toward the profession of teaching.3. Initiating a program for training teachers of Quran Sciences and IslamicEducation in the light of the needs of the applicant students.